Dimethyl 4,5-dichlorophthalate - Daniel D. Hickstein (International Union of Crystallography, 2021)
While endeavoring to synthesize new chlorinated ligands for ruthenium-based metathesis catalysts, the title compound dimethyl 4,5-dichlorophthalate, C10H8Cl2O4, was prepared from commercially available 4,5-dichlorophthalic acid in ∼77% yield. The title molecule, which also finds utility as a precursor molecule for the synthesis of drugs used in the treatment of Alzheimer's disease, shows one carbonyl-containing methyl ester moiety lying nearly co-planar with the chlorine-derivatized aromatic ring while the second methyl ester shows a significant deviation of 101.05 (12)° from the least-squares plane of the aromatic ring. Within the crystal, structural integrity is maintained by the concerted effects of electrostatic interactions involving the electron-deficient carbonyl carbon atom and the electron-rich aromatic ring along the a-axis direction and C—H...O hydrogen bonds between neighboring molecules parallel to b.